Promote Global Peace, Health and Entrepreneurship Using Human Anatomical Structures: Sexual Satisfaction, Husband or Wife’s Responsibility? Part 1 - Niriwa, Benjamin Pulle; Gyamea, Helina; Dumba, James; Kwame, Nyinaku Elorm; Asaana, David Akusi; Ampofo, Deborah; Ibrahim, Mohammed M.; Alorvi, Semefa; Barima, Antwi Joseph; Agyemang-Badu, Samuel Yaw; Allotey, Solomon Saka; Batuu, Elvis; et al. (International Journal of Innovative Research in Medical Science, 2022)
The recent increase in legally married couples ignoring each other’s sexual needs, though, it is one of the pillars for happy marriage must be a headache to all. It is an open secret nowadays to see and hear married partners complaining bitterly about being sexually neglected. What is worrying is that; although men hitherto were not known for ignoring sexual demands of their wives, now women also complaint of their husbands avoiding them. Shockingly, these same couples are mostly later caught red handed cheating. Cheating used to be popular amongst only men but now women are also well known for cheating on their husbands. But strangely, women who cheat have rebranded cheating; especially with their co-workers as “Office husbands”. Likewise, many men have shared their painful experiences of catching their wives whilst they were also in the act of cheating. These are mostly as a result of partners’ inability to fully sexually satisfy each other in bed. Increasing refusal of partners to have sexual intimacy has not only contributed to increasing breaking homes and domestic violence, but homicides. Homicide especially in the Latin America and Caribbean (LAC) region is the highest in the world that targets mostly young males. Evidence shows that sexual satisfaction during intercourse is one of the oils that is greasing family peace. One of the ways partners would surprise themselves often in bed and have stronger bonds; is by appreciating the roles that sensitive anatomical structures of their bodies play in making them sexually and emotionally satisfied. But there is little available literature linking the anatomy, physiology and psychology of humans’ love, romance, and sexual satisfaction. To help promote individuals and family harmony for global peace, quality health and entrepreneurship; this review was done to help educate couples and the public on how the anatomies and physiologies of their bodies after helping them win love can also help them maintain it. Through this review too, partners would also appreciate their anatomical structures and how they can help them not to only enjoy sexual intercourse but have orgasm. This review is also to encourage couples to freely communicate their feelings and how their partners should satisfy them. Sexual rejection by married partners would further increase with associated increasing cheatings, incest, break ups, and even homicides if nothing is done. This review would help legally married people identify how to satisfy their sexual needs and stay strongly bonded in their marriages. This will also contributes to peaceful and healthy families who can work for economic development.